Formamidinium containing tetra cation organic–inorganic hybrid perovskite solar cell. (15th May 2021) - Singh, Harish; Dey, Pritam; Chatterjee, Shovon; Sen, Pratik; Maiti, Tanmoy
Highlights: Synthesized thin films of halide perovskites with triple cations (Bi, Pb, Na/K) at B-site. Exhibited good absorption coefficient, good charge carrier lifetime. Unraveled ultrafast carrier dynamics using femtosecond transient absorption studies. Faster free electron-hole recombination process found in FKBPI compared to FNBPI. Degradation studies carried out by XRD, UV–Vis, TCSPC and DSC-TGA over 15 days. Multiple cations in B-site produced stable organometallic halide photovoltaics. Abstract: ABX3 perovskites offer the advantage of manipulating its properties by introducing multiple cations in B-site. Over the years, researchers used mixed B-site perovskites in oxide electronics to tune their electrical, magnetic properties. Here we used the triple cations at B-site in formamidinium based organometallic halide perovskite solar cell (PSC) in order to improve its degradation behavior with respect to heat and moisture. We synthesized halide based two hybrid perovskites viz., formamidinium sodium bismuth lead iodide [NH2 CHNH2 (Na0.25 Bi0.25 )Pb0.5 I3 ] and formamidinium potassium bismuth lead iodide [NH2 CHNH2 (K0.25 Bi0.25 )Pb0.5 I3 ] using solution chemistry. In order to decrease the content of toxic lead in these perovskites, trivalent bismuth was incorporated in the Pb-site. Monovalent sodium and potassium were used to maintain the charge neutrality of B-site, which has the formal valence of + 2 in these ABI3 type perovskites. Both of these perovskites showed reasonable optical band gaps with good charge carrier lifetime suggesting it as potential candidates for solar energy conversion and provisionally we achieved power conversion efficiency η = 0.52%. Moreover, superior thermal and moisture stability in these perovskites were observed in periodical structural and spectral analysis carried out by XRD, UV–Vis spectroscopy, time-correlated single photon counting (TCSPC) over the period of one month. Furthermore, ultrafast carrier dynamics in these perovskites were unraveled using femtosecond transient absorption studies. Our transient absorption kinetics data suggested more auger recombination and faster free electron-hole recombination process in FKBPI compared to FNBPI, which corroborates well with better energy conversion efficiency obtained in FNBPI based solar cell.